Effect of graded laminectomy and facetectomy on biomechanical properties of normal lumbar spine : a finite element study - Shukri, Farid Fikri (2018)
Graded laminectomy and facetectomy are techniques for decompressing neural structure in the lumbar spine. However this resection techniques normally lead to a decrease in spinal stability. Previous experimental studies were based on in vitro human cadaver model to determine the instability of lumbar spine following graded decompression surgery. However, there are some major limitations in these experimental studies in which the inability to determine the intrinsic parameters such as loads, stresses and strains over the intervertebral disc and vertebra bodies after the surgery. In order to investigate spinal stability and the intrinsic parameters after decompression spinal surgery, a finite element analysis of the lumbar spine was performed. Intersegmental motions of lumbar vertebrae, stresses of intervertebral disc and vertebra bodies were calculated while simulating an intact spine as well as different extents of resection (hemilaminectomy, hemifacetectomy, total laminectomy and total facetectomy). METHODOLOGY A three-dimensional, non-linear finite element model of the lumbar spine was created using Mimic 10.01 software and meshed using 3-Matic 11.0 software . Only one model of lumbar finite element L1-L5 was constructed from a normal lumbar CT images, and this finite element model was extrapolated to represent the human population with normal lumbar spine. Since no in vitro experiment is done in our study, the validation of our finite element model is based on previous experimental study. Then, spinal decompression procedures are simulated on the lumbar model using Marc Mentat 2010 software. There is no statistical analysis as the result is analysed directly from decompression surgery of one normal lumbar model, hence, there is no hypothesis in our study. RESULT For surgery that preserved the spinous process (hemilaminectomy, hemifacetectomy and total facetectomy), the displacement of the spine are 1.31o, 1.20o, 1.37o. However, when the spinous process is resected (laminectomy), the displacement of the spine in flexion rise up to 3.43o which was increased 4.53% compared to intact model. The displacement of lumbar spine in extension post decompression surgery are 1.85o, 1.87o, 1.91o and 1.95o. The result showed near equal displacement of lumbar spine in extension after each simulation surgery. There is high stress concentration post decompression surgery over anterior aspect of the intervertebral disc L3/L4 in flexion group otherwise low in extension group. The increased , stress concentration on vertebra bodies also produce different pattern in each decompression surgery during flexion and extension. CONCLUSION Graded laminectomy and facetectomy of lumbar spine in finite element analysis shows increase in intersegmental motion that lead to spinal instability. In our study, total laminectomy affect stability the most by having more intersegmental mobility and most intervertebral disc stress in flexion. Total facetectomy affect the intervertebral disc stress more in flexion but only have slight increase of intersegmental motion in flexion. This shows that total laminectomy produce the most instability compared to total facetectomy.